2018
DOI: 10.1037/tps0000153
|View full text |Cite
|
Sign up to set email alerts
|

Early elementary school children’s conceptions of neighborhood social stratification and fairness.

Abstract: In a time of unprecedented levels of income inequality, American adults support a more equitable distribution of wealth, but little is known about how children think about social stratification. This study examined children's understanding of social stratification and their evaluations of whether the stratification was fair. Participants were 5-to 8-year-old children (n ϭ 86, M age ϭ 6.81, SD ϭ .93) who were from primarily upper-middle class, racially and ethnically diverse families and attending a universitya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…However, these findings resonate with those from recent studies indicating that even young children may have a general sense of their family’s economic status (Elenbaas 2019 ; Hazelbaker et al 2018 ), though these perceptions are not as complex, nuanced, or calibrated as those of adolescents or adults. The results of this study highlight a need for further research on the early origins and development of children’s perceptions of family economic stress and SSS, as these correlate with parents’ perceptions and relate to academic adjustment earlier in development than previously anticipated.…”
Section: Discussionsupporting
confidence: 82%
“…However, these findings resonate with those from recent studies indicating that even young children may have a general sense of their family’s economic status (Elenbaas 2019 ; Hazelbaker et al 2018 ), though these perceptions are not as complex, nuanced, or calibrated as those of adolescents or adults. The results of this study highlight a need for further research on the early origins and development of children’s perceptions of family economic stress and SSS, as these correlate with parents’ perceptions and relate to academic adjustment earlier in development than previously anticipated.…”
Section: Discussionsupporting
confidence: 82%
“…Already in their first year of life, infants notice when someone has more toys than someone else (Sommerville, 2018). By the time they reach kindergarten, children attend to wealth inequalities, identifying their peers as “poor” or “rich,” alongside other forms of social categorization (e.g., gender, ethnicity; Hazelbaker, Griffin, Nenadal, & Mistry, 2018; Shutts, 2015). Over the course of adolescence, youths view U.S. society as increasingly economically stratified and also increasingly link economic status and race, associating White and Asian Americans with higher income and wealth than Black and Latinx Americans (Arsenio & Willems, 2017; Ghavami & Mistry, 2019).…”
Section: Awareness Of Social Inequalitiesmentioning
confidence: 99%
“…It has been demonstrated that the local socioecological (environmental) conditions people are exposed to during childhood shape many facets of adult life (15)(16)(17), including social behavior (18)(19)(20)(21)(22). Indeed, recent research indicates that by 8 years old, and even earlier, children understand local economic inequality and perceive it as unfair (23,24).…”
Section: Introductionmentioning
confidence: 99%